Effect of Foliar Application of Salicylic Acid on Enhancing Salinity Tolerance in Sorghum (Sorghum bicolor L.): Foliar application of salicylic acid for enhancing salinity tolerance - Mrudhula K, Anny; Vani P, Madhu; Kumar M, Sunil; Latha A, Suvarna (Journal of Soil Salinity and Water Quality, 2025)
Salinity represents a major abiotic constraint that adversely affects crop productivity, particularly in arid and semi-arid regions. Under saline conditions, plant growth and development are primarily hindered by physiological drought, ionic toxicity resulting from excessive accumulation of sodium (Na+) and chloride (Cl-) ions, and the generation of reactive oxygen species (ROS) such as superoxide radicals, hydrogen peroxide, hydroxyl ions, and singlet oxygen within chloroplasts, mitochondria, and the apoplastic space. To address the impact of salinity stress, a field experiment was conducted during the Kharif seasons of 2023, 2024, and 2025 at a farmer’s field in Kakarlamoodi village. The objective was to evaluate the efficacy of foliar application of salicylic acid in enhancing salinity tolerance in sorghum. The study was structured using a randomized block design comprising six treatments, each replicated four times. Five concentrations of salicylic acid (50, 100, 150, 200, and 250 mg L-¹) were applied, along with a control treatment. The results demonstrated that the 250 mg L-¹ salicylic acid treatment significantly improved grain yield (5729, 6235 and 6300 kg ha-¹), whereas the lowest yield was recorded under the control treatment. In addition to yield enhancement, the highest values for total chlorophyll content, antioxidant enzyme activity, protein concentration, and potassium accumulation in both grain and straw were observed with the 250 mg L-1 foliar application, indicating its effectiveness in mitigating the adverse effects of salinity.